2003
DOI: 10.1177/0020872803046002003
|View full text |Cite
|
Sign up to set email alerts
|

Using Single-system Research Designs to Evaluate Practice

Abstract: The use of single-system research designs (SSRDs) has the potential to help social workers empirically evaluate the outcomes of practice. Descriptions of using SSRDs to evaluate social work practice are provided. SSRDs have the potential to help social workers in Chinese contexts to provide scientifically credible evidence to others that social services benefit the people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Convenience sampling is commonly used in social service settings, as social service research often faces practical limitations such as time constraints or logistical challenges (Holosko et al 2013;Thyer et al 2003). Researchers sometimes use convenience sampling for pilot testing, gathering data from a small sample to refine the instruments or programs before conducting a more extensive study.…”
Section: Selection Of Reader Participants From Three Types Of Activitiesmentioning
confidence: 99%
“…Convenience sampling is commonly used in social service settings, as social service research often faces practical limitations such as time constraints or logistical challenges (Holosko et al 2013;Thyer et al 2003). Researchers sometimes use convenience sampling for pilot testing, gathering data from a small sample to refine the instruments or programs before conducting a more extensive study.…”
Section: Selection Of Reader Participants From Three Types Of Activitiesmentioning
confidence: 99%
“…The use of single-system research designs (SSRDs) is compatible with the pragmatic focus of social workers who use practical methods to evaluate agency problems, social policies, and direct practice interventions (Thyer, Artelt, & Shek, 2003). With an increasing demand for accountability and quality in service provisions, social workers find it necessary to collect scientifically credible evidence to show if their programs or interventions produce favorable outcomes.…”
Section: Activity 2: Using Assessment Templates For Critical Evaluatimentioning
confidence: 99%
“…Additionally, a request to fund the continuation of a successful project could be more persuasive if a practice research study had been conducted to provide evidence using appropriate evaluative methods (Rock & Cooper, 2000; Thyer, Artelt, & Shek, 2003). Thirdly, practice research has been found to increase enthusiasm for research among practitioners (McCrystal, 2000) and improve their confidence and motivation to do research (Joubert, 2006).…”
Section: The Potential Benefits Of Practice Research In Chinamentioning
confidence: 99%